Evaluation of Latex Agglutination Test (KAtex) for Early Diagnosis of Kala-azar - Ahsan, MM; Islam, MN; Mollah, AH; Hoque, MA; Hossain, MA; Begum, Z; Islam, MT (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):335-9. The abstract of this article is available on the PubMed website